2017
DOI: 10.12659/msm.902971
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognostic Factors in Bone Metastases from Lung Cancer

Abstract: BackgroundThis study investigated the prognostic factors of bone metastases from lung cancer.Material/MethodsFrom March 2014 to March 2015, 168 patients with bone metastases from lung cancer treated at our hospital were included and the clinical data were reviewed. The Kaplan-Meier survival curves were calculated and analyzed using the log-rank univariate test. Multivariate regression analysis was conducted using Cox’s regression model.ResultsThe overall median survival of the 168 patients was 13 months. The 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
82
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 22 publications
8
82
0
4
Order By: Relevance
“…Therefore, ALP has been extensively used to screen patients for bone metastasis. Some studies have shown that the baseline ALP level and changes in the ALP level can predict treatment effects and survival in bony metastatic cancers . After analyzing 168 lung cancer patients, Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ALP has been extensively used to screen patients for bone metastasis. Some studies have shown that the baseline ALP level and changes in the ALP level can predict treatment effects and survival in bony metastatic cancers . After analyzing 168 lung cancer patients, Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing 168 lung cancer patients, Zhang et al . reported that the serum ALP level is a prognostic factor for bone metastases in lung cancer and that a higher serum ALP level is associated with shorter survival …”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related deaths worldwide, with 50-70% of patients suffering from bone metastasis [1][2][3][4][5] . Detrimental skeletal-related events are more common in end-stage patients and are associated with significant morbidity [6][7][8] .…”
mentioning
confidence: 99%
“…24,25 It is commonly recognized to have high diagnosis specificity in bone metastasis and has been reported in certain bony metastasis malignancies. [26][27][28] Additionally, ALP was found to influence inflammation through regulation of purinergic signaling and induce an inhibitory immune response. 29 Besides, ALP can be generated and released into the blood directly by tumor cells and regulates tumor growth.…”
Section: Discussionmentioning
confidence: 99%